Toxic equivalency factors (TEFs) after acute oral exposure of azaspiracid 1, −2 and −3 in mice. (5th January 2018) - Pelin, M.; Kilcoyne, J.; Nulty, C.; Crain, S.; Hess, P.; Tubaro, A.; Sosa, S.
Graphical abstract: Highlights: Azaspiracids (AZAs) are marine algal toxins contaminating edible shellfish. In the EU, only AZA1, −2 and −3 are currently regulated in edible shellfish. AZA1-3 concentration in seafood is determined by Toxicity Equivalency Factors (TEFs). TEFs are derived by AZA1-3 intraperitoneal lethal potency in mice. Due to the dietary exposure to AZAs, new oral TEFs were derived for AZA1, −2 and −3. Abstract: Azaspiracids (AZAs) are marine algal toxins that can be accumulated by edible shellfish to cause a foodborne gastrointestinal poisoning in humans. In the European Union, only AZA1, −2 and −3 are currently regulated and their concentration in shellfish is determined through their toxic equivalency factors (TEFs) derived from the intraperitoneal lethal potency in mice. Nevertheless, considering the potential human exposure by oral route, AZAs TEFs should be calculated by comparative oral toxicity data. Thus, the acute oral toxicity of AZA1, −2 and −3 was investigated in female CD-1 mice treated with different doses (AZA1: 135–1100 μg/kg; AZA2 and AZA3: 300–1100 μg/kg) and sacrificed after 24 h or 14 days. TEFs derived from the median lethal doses (LD50 ) were 1.0, 0.7 and 0.5, respectively for AZA1, −2 and −3. In fact, after 24 h from gavage administration, LD50s were 443 μg/kg (AZA1; 95% CL: 350−561 μg/kg), 626 μg/kg (AZA2; 95% CL: 430−911 μg/kg) and 875 μg/kg (AZA3; 95% CL: 757−1010 μg/kg). Mice dead more than 5 h after the treatment or those sacrificed after 24 h (doses: ≥175 μg AZA1/kg, ≥500 μg AZA2/kg and ≥600 μg AZA3/kg) showed enlarged pale liver, while increased serum markers of liver alteration were recorded even at the lowest doses. Blood chemistry revealed significantly increased serum levels of K + ions (≥500 mg/kg), whereas light microscopy showed tissue changes in the gastrointestinal tract, liver and spleen. No lethality, macroscopic, tissue or haematological changes were recorded two weeks post exposure, indicating reversible toxic effects. LC–MS/MS analysis of the main organs showed a dose-dependency in gastrointestinal absorption of these toxins: at 24 h, the highest levels were detected in the stomach and, in descending order, in the intestinal content, liver, small intestine, kidneys, lungs, large intestine, heart as well as detectable traces in the brain. After 14 days, AZA1 and AZA2 were still detectable in almost all the organs and intestinal content.